Hopes and lost illusions. Balkan Wars in the light of the texts from the circle Dimitrija Čupovski and Krste P. Misirkov - Moroz-Grzelak, Lilla (Balcanica Posnaniensia. Acta et studia, 2012)
This article addresses the sense of national identity of the Macedonians in the period of the Balkan wars and their aftermath. The first source material were used journalistic texts and calls in the journal „Makedonskij Golos” published by Macedonian expatriates gathered around Dimitrija Čupovski in St. Petersburg in the years 1913-1914. Second was diary <span style="font-family: 'Times New Roman','serif'; font-size: 12pt; mso-fareast-font-family: TimesNewRomanPS-ItalicMT; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Dnevnik) written by Krste Petkov Misirkov in 1913. Expression of these two major characters in the Macedonian history reflect geopolitical policies conducted in the Slavic population in the Balkans. It is an important source material documenting the national consciousness of intelligence derived from the Macedonian lands. This indicates that the main topics which were then undertaken focused on the defense of the whole Macedonian territory, aspirations to create their own state and diversified approach to the idea of the Slavic community.